FAKTOR PENGHAMBAT PELAKSANAAN PUTUSAN TUN OLEH PEJABAT TATA USAHA NEGARAStudi kasus: Putusan No.8/G/2022/PTUN.MDN - Gunawan Widjaja; Adi Rumanto Waruwu (Adisam Publisher, 2024)
The application of the principle of the rule of law in Indonesia has led to the emergence of state administrative courts. The establishment of the State Administrative Court is a legal eflort that can be taken by the public to protect their rights from the arbitrariness of state administrative officials. The purpose of establishing the State Administrative Court is to balance the position of Administrative Officials and the public as plaintifls. As a judicial institution, the content of the judge's ruling should be respected and must be obeyed by the litigating official. But in reality, so many officials do not comply and implement it. Even though the verdict has been pronounced by the judge and has legal force, seeing the attitude of officials who do not want to implement the decision seems to disrespect the judge's decision and can be interpreted as a form of resistance to non- compliance. Therefore, this research discusses extensively through a normative point of view regarding the lack of compliance of state administrative officials and what eflorts the plaintifl can make to ensure that the decision is implemented to the fullest.